The Influence of Occupational Safety and Health on Employee Performance which is Mediated by Employee Work Motivation at PT PIP - Suyatno; Pancasasti, Ranthy (Journal of Business and Behavioural Entrepreneurship, 2023)
Background: Employee performance is an aspect that must be considered by every company. Because if the employee's performance is not good, it will affect the progress and development of the company in the future. However, in recent years the performance of employees at PT PIP has decreased. Many factors affect the decline in employee performance at PT PIP, one of which is the occurrence of work accidents due to inconsistent implementation of Occupational Safety and Health, resulting in decreased employee motivation. Purpose: This study aims to examine and analyze the variables that can affect employee performance with Occupational Safety and Health at PT PIP through employee motivation as mediation. Originality/Value: Updates in this research have not been found in previous research discussing efforts to improve employee performance by implementing the Occupational Safety and Health program and employee motivation at PT PIP. Research Limitations: The limitations in this study are only to analyze efforts to increase employee performance with Occupational Safety and Health and employee motivation at PT PIP. Research Design/Methodology: In this study, a quantitative descriptive method was used. There are 2 types of data sources used in this study, namely primary data and secondary data. The population in this study were all permanent employees of PT PIP. In this study, a saturated sample was used for the sampling method, which means that all the people in the population are used as the sample. As a result, all permanent employees of PT PIP or 103 respondents became the research sample. Findings: Based on the research results show that Occupational Safety and Health has a positive effect on employee performance but not significant. Occupational Safety and Health has a positive and significant effect on employee motivation. Employee motivation has a positive effect on employee performance. Employee motivation mediates the effect of Occupational Safety and Health on employee performance.